(untitled) (Nonconventional Technologies Review, 2024)
Aluminium alloys are widely employed across numerous thanks to their superior combination of strength, lightweight characteristics and corrosion resistance. In recent years, Friction stir processing (FSP) has come up as a promising technique for machining aluminium alloys, enabling greater control over microstructural evolution and mechanical properties. This paper provides an in-depth exploration the impact of process parameters on the microstructure and mechanical properties of aluminium alloys processed by FSP. The study focuses on the systematic investigation of the influence of the principle process parameters, including rotational speed, machining speed and applied pressure, on the microstructure and resulting mechanical performance of FSP machined aluminium alloys. Furthermore, the mechanical properties of FSP treated aluminium alloys are measured by a comprehensive set of tests, including tensile tests, hardness measurements and fracture tests. The relationship between process parameters and the mechanical behaviour of the alloys is analysed in detail to identify the optimum conditions for achieving the desired properties. Findings show that process parameters plays a significant role in defining the microstructure and mechanical properties of alloys.